A literature review on the potential clinical implications of streptococci in gastric cancer - Zi, Mengli; Zhang, Yanqiang; Hu, Can; Zhang, Shengjie; Chen, Jinxia; Yuan, Li; Cheng, Xiangdong (Frontiers in Microbiology, 2022)
Streptococcus is widely found in nature and the human body, and most species are not pathogenic. In recent years, studies have found that Streptococcus is associated with gastric cancer. Streptococcus was found to be enriched in the oral cavity, stomach and intestine of gastric cancer patients and found to be increased in gastric cancer tissues, suggesting that Streptococcus may be the pathogenic bacteria underlying gastric cancer. This review discusses the discovery of Streptococcus, the relationship between Streptococcus and gastric cancer, and the possible carcinogenic mechanism of Streptococcus and summarizes the progress of the research on the role of Streptococcus in gastric cancer to provide new ideas for the early detection, diagnosis and treatment of gastric cancer.